Mechanisms of resistance to β-lactam antibiotics in Bacteroides species - Edwards, Richard (1995)
Mechanisms responsible for resistance to β-Iactam antibiotics were investigated in clinical isolates of Bacteroides spp., the most common anaerobic Gram negative pathogen. Among 108 isolates of Bacteroides spp. obtained from clinical material in Nottingham, 69 (64%) were identified as Bacteroides fragilis. Approximately one-fifth of the Bacteroides spp. produced elevated levels of β-Iactamases, and many of these strains showed increased resistance to β-Iactam antibiotics usually regarded as β-Iactamase stable.